Litanies Near Water : Poems - Buck, Paula Closson (Book collections on Project MUSE., 2008)
Infused with Mediterranean landscapes, the poems of Litanies Near Water, Paula Closson Buck''s second collection, probe the world through language that acts sometimes like a divining rod and sometimes like a lightning rod. Elegant meditative lyrics such as ""You Cannot Love the Wind"" and ""Theory of an Impersonal God"" answer to politically alert poems like ""Monk Killed by Tractor in Bid to Dodge Police."" Ultimately, in Buck''s deft hand, the lyrical quest for understanding becomes a form of diplomacy between the physical and the metaphysical, between instances of beauty and the violence th.